The Effects of European Economic and Monetary Union on Wage Behaviour - Charlotte Lauer (Institute for the Study of Labor (IZA), 1999)
This paper evaluates the possible consequences of the forthcoming European and Monetary Union on wage behaviour. It will be shown that EMU does not influence wage policy directly, but rather indirectly through its implications on other areas of economic policy, predominantly on monetary policy. Consequently, EMU will put increasing pressure on using wage policy as a flexible adjustment variable, since other adjustment mechanisms shall cease to exist. Six European countries were analysed empirically, which showed that in the past, southern European countries conducted a much more expansive wage policy than northern European countries. However, this competitive disadvantage of the southern countries was more than compensated by exchange rate developments. What will happen when EMU has come into effect? Either fewer devaluation possibilities within EMU will lead to a shift in competitive positions in favour of the northern countries, or a change in wage behaviour will be observed. The descriptive analysis shows that, on the eve of EMU, wage policy has become more moderate. This trend could be accelerated by the arrival of EMU. The econometric analysis provides an argument for this: the stability of exchange rates have been proven to have a dampening effect on wage increases in the past, particularly in southern European countries. Whether the extent of these effects will be sufficient to prevent a shift in relative competitive positions, however, remains to be seen.
Keywords: E52; E24; J20; 330; European Monetary Union; Euro; wage behaviour; wage policy; Lohnpolitik; Wirtschaftliche Anpassung; Europäische Wirtschafts- und Währungsunion; Schätzung; Niederlande; Deutschland; Frankreich; Italien; Spanien; Portugal